Análises hierárquica e de regressão linear aplicadas aos mapeamentos de suscetibilidade e de risco aos movimentos de massa (bairro Cidade Nova, Aracaju – SE, Brasil) - Franco, Luisa Sampaio (2021)
The municipality of Aracaju, capital of Sergipe, preserves on its peripheral landscape, at the northern region, coastal tablelands with elevations of up to 100 m above sea level, and land slopes above 30º, naturally favorable to the occurrence of gravitational mass movements. In the years 2000 and 2010, the region, specifically the Cidade Nova Neighborhood, the area of the present study, suffered the intensification of slope cuts for housing construction, which has resulted in discrete events of landslides, with material losses, leaving residents at risk of death in the rainy season. As a way of contributing to the reduction of geological risk, which has been monitored in a qualitative way, under a minor detail scale, a semi-quantitative mapping was proposed in the present work. The analytic hierarchy process (AHP) and linear regression methods were adopted with the aim of mapping both susceptibility and geological risk. The combination of weighted parameters (slope, flow density, lithology, hypsometry) in a GIS software, with photointerpretation of satellite images and oblique aerial images, showed that 3.08% of the land cover is under very high susceptibility to mass movements, comprising 356 houses under a landslide risk, which required a detailed house-to-house scale mapping. Fieldwork and the use of AHP method allowed the identification of 43 risk sectors susceptible to landslides, comprising 4 sectors under very high degree of risk and 9 under high risk, respectively, a gain of 80 % and 75 % compared to the previous study. Despite that, it was registered a reduction of 61,6% of people under very high risk and 57% under high risk, demonstrating the importance of the method.